Age-related biochemical dysfunction in 6-OHDA model rats subject to induced- endurance exercise - Rezaee, Zeinab; Marandi, Sayed Mohammad; Esfarjani, Fahimeh (Archives of gerontology and geriatrics, 2022)
•6-OHDA injection impairs mitochondrial and behavioral function of the subjects groups•Dysfunctions caused by Parkinson's disease are greater in old rats•Endurance treadmill exercise reduces the neurochemical deficit after 6-OHDA lesion•The neuroprotective effects of exercise are greater in young rats with Parkinson's Disease•The beneficial effects of endurance exercise in 6-OHDA-induced rats are age-related•Our research corroborates the protective effects of exercise on the molecular functions in rat model of Parkinson's Disease. Exercise can alleviate the disorders considered as the normal consequences of aging. Whether or not the treadmill endurance training affects the biochemical markers in the Parkinson's disease model rats after the 6-hydroxydopamine (6-OHDA) injection is assessed in this article. The experimental groups of N=8 rats consist of 1) Saline and Young sedentary (S-Young); 2) Saline and Old sedentary (S-Old); 3) Young and 6-OHDA without exercise (Y); 4) Young and 6-OHDA with exercise (YE); 5) Old and 6-OHDA without exercise (O); and 6) Old and 6-OHDA with exercise (OE). An 8 μg of 6-OHDA is injected into the right MFB. The rotation due to apomorphine, weight variation, and some biochemical expression are measured in the rats’ striatum. Exposure to 6-OHDA: increase weight loss by (%8) and rotation by (%90), reduce the protein levels of Bdnf by (30%), Th by (43%), and Tfam by (24%), in aging rats (P<0.05). The P53 level rose after the injection compared with the same Saline group (Old rats: 27% and Young rats: 14%), the highest in the O group. The findings indicate that endurance exercise amends the mitochondrial parameters and the apomorphine-induced rotation impairments in the presence of 6-OHDA injection. These positive effects of treadmill running in unilateral 6-OHDA lesioned rat model are age-dependent and are more significant in younger rats.